Sumo : - Sargeant, J. A. (Charles E. Tuttle, 1963)
A treatment of Japan's national sport from its prehistoric origins to the present, explaining diet, training, holds and throws, rules and rankings. The book's appendices provide vital statistics on the great yokozuna champions and information on the new stadium